Lateral preference in Williams-Beuren syndrome is associated with cognition and language. - Pérez-García, D.; Flores, R.; Brun-Gasca, C.; Pérez-Jurado, L. (European Child & Adolescent Psychiatry, 2015)
Williams-Beuren syndrome (WBS) is a genetically defined neurodevelopmental disorder presenting with intellectual disability associated with a specific neurocognitive profile characterized by anxiety, hypersociability, poor visuospatial skills and relatively preserved language. We have defined the lateral preference in 69 individuals (40 males and 29 females, age range 5-47 years) with WBS confirmed by molecular testing, and explored its correlation with cognition, behavior problems, the main aspects of the behavioral phenotype, and specific molecular variants (parental origin and size of the 7q11.23 deletion). Lateral preference (hand, foot, eye and ear) and neurobehavioral features [intelligence quotient (IQ), sociability, visuospatial construction, narrative skills and behavior] were assessed by a battery of tests and parental interviews. A large proportion of WBS individuals showed either left or mixed handedness (26 and 19 %, respectively). Hand, foot and ear lateral preference showed significant association with IQ, with individuals with mixed lateral preference presenting lower general IQ, especially verbal IQ, with respect to subjects with well-defined laterality. Approachability, visuospatial ability, behavior problems or molecular variants were not associated with lateral preference. Our results indicate that, as in other neurodevelopmental disorders, laterality is poorly defined in a significant proportion of WBS individuals, and reinforces the idea that a correct definition of lateral preference is important for cognition and language.